Polymer blends of poly(2-cyanoethyl vinyl ether) and poly(methyl methacrylate) with improved dielectric properties for flexible electronics - F. Piana; J. Kredatusova; B. Paruzel; J. Pfleger (eXPRESS Polymer Letters)
There is a big demand for the development of polymer materials for flexible electronics, among them polymers with a high dielectric constant play an important role. Here the preparation and properties of a polymer blend composed of poly(2-cyanoethyl vinyl ether) (CEPVA) as an amorphous polymer with dielectric constant (ε') ~ 15 but glass temperature (Tg) close to room temperature, and poly(methyl methacrylate) (PMMA), a polymer with low ε' ~ 5 and high Tg, are reported. The film forming ability, structure and dielectric properties of the blend are reported to verify its applicability for capacitors and field effect transistors. PMMA:CEPVA ratios 10:90 and 30:70 represent the best composition for obtaining a monophasic system with increased dielectric constant and Tg well above the room temperature. The improved properties have been attributed to the impact of PMMA on the relaxation phenomena of CEPVA, namely to an increased mobility of cyano-groups responsible for the dielectric behavior, as it was observed by the broadband dielectric and nuclear magnetic resonance (NMR) spectroscopies.